Non-targeted metabolomic study in plasma in rats with post-traumatic osteoarthritis model - Han, Peng-fei; Li, Xi-yong; Zhang, Chang-peng; Liao, Chang-sheng; Wang, Wei-wei; Li, Yuan (PloS one, 2025)
This study aimed to examine the differential expression profiles of plasma metabolites in rat models of post-traumatic osteoarthritis (PTOA) and elucidate the roles of metabolites and their pathways in the progression of PTOA using bioinformatics analysis. Plasma samples were collected from 24 SD female rats to model PTOA, and metabolomic assays were conducted. The samples were divided into three groups: the surgically induced mild PTOA group (Group A: 3 weeks postoperative using the modified Hulth model; age 2 months), the surgically induced severe PTOA group (Group B: 5 weeks postoperative using the modified Hulth model; age 2 months), and the normal control group (Group C: healthy rats aged 2 months). Metabolites were structurally identified by comparing the retention times, molecular masses, secondary fragmentation spectra, collision energies, and other metabolite data with a database (provided by Shanghai Applied Protein Technology Co., Ltd.). Target prediction and pathway analysis were subsequently performed using bioinformatics analysis. The experiment revealed that in the mild PTOA group, levels of Alpha-ketoglutarate, Isocitric acid, Dichloroacetate, and other metabolites increased significantly compared with the normal group, whereas Linolenic acid, Lactose, and others decreased significantly. These findings suggest that these metabolites can serve as biomarkers for the diagnosis of early PTOA. In the severe PTOA group, Diosgenin, Indoleacrylic acid, Alpha-ketoglutarate, Isocitric acid, and others were elevated and may also be used as biomarkers for PTOA diagnosis. Adrenosterone, (+)-chlorpheniramine, and Phenanthridine levels were higher in the severe PTOA group compared to the mild PTOA group, while Menadione, Adenosine 5'-monophosphate, and Arg-Gly-Asp levels were lower. Taurocholate, indoleacrylic acid, alpha-ketoglutarate, and isocitric acid may serve as biomarkers for PTOA joint injury in rats. Menadione, adenosine 5'-monophosphate, and Arg-Gly-Asp exhibited differential expression between severe and mild PTOA groups in rats, potentially reflecting the injury's severity. Further investigation into these molecules in human tissues is warranted to ascertain their utility as biomarkers for PTOA in humans.